ANALISIS METAKOGNISI SISWA SMP NEGERI I BUKO DALAM MEMECAHKAN MASALAH MATEMATIKA - Fitrianti (Linear : Jurnal Ilmu Pendidikan, 2018)
This research aimed to describe student’s metacognition in solving mathematics problem. The research subjects were two students of class VII of a junior high school in Buko. The two subject represented types of components metacognition i.e one student has cognition knowlwdge and another has cognition regulation. Research instruments were metacognitive awareness inventory, mathematics understanding test and interview protocol. Research data were collected by using student’s answer sheets and interviews. The data were analyzed by descriptive method. Based on the analysis, it can be concluded that: (1) NDM student performend her cognition knowledge in the problem solving stages, and it depends on her knowledge types (declarative, procedural, dan conditional knowledge); and (2) PSV student performend characteristics of cognition regulation and they depend on each stage in the problem solving.